Conditional disease‐free survival after curative‐intent liver resection for neuroendocrine liver metastasis. Issue 7 (24th September 2019) - Sahara, Kota; Merath, Katiuscha; Tsilimigras, Diamantis I.; Hyer, J. Madison; Guglielmi, Alfredo; Aldrighetti, Luca; Weiss, Matthew; Fields, Ryan C.; Poultsides, George A.; Maithel, Shishir K.; Endo, Itaru; Pawlik, Timothy M.; et al.
Abstract: Background: Neuroendocrine liver metastases (NELM) are typically associated with high recurrence rates following surgical resection. Conditional disease‐free survival (CDFS) estimates may be more clinically relevant compared to actuarial survival estimates. Methods: CDFS was assessed using a multi‐institutional cohort of patients. Cox proportional hazards models were used to evaluate factors associated with disease‐free survival (DFS). Three‐year CDFS (CDFS3) estimates at "x" year after surgery were calculated as CDFS3 = DFS(x + 3)/DFS(x). Results: A total of 521 patients met the inclusion criteria. While actuarial 3‐year DFS gradually decreased from 49% at 1 year to 39% at 5 years, CDFS3 increased over time. CDFS3 at 5 years was estimated as 89% vs actuarial 8‐year DFS of 39% ( P < .001). The probability of remaining disease‐free at 5 years after resection increased as patients remained disease‐free. For example, the probability of being disease‐free for an additional 3 years was 66.3% and 88.8% for patients who lived 2 and 5 years, respectively. Overall, CDFS3 in each subgroup increased postoperatively as years elapsed, however, the impact of each prognostic factor on CDFS3 changed over time. Conclusion: CDFS of patients who underwent resection of NELM exponentially improved as patients survived additional years without recurrence. CDFS provides more accurate prognostic measures compared with traditional DFS measures.